Protective Role of Melatonin Against Postmenopausal Bone Loss via Enhancement of Citrate Secretion From Osteoblasts - Da, Wacili; Tao, Lin; Wen, Kaicheng; Tao, Zhengbo; Wang, Shaojie; Zhu, Yue (Frontiers in Pharmacology, 2020)
There is a negative correlation between the severity of osteoporosis and the level of citrate in bone. Our previous research found that melatonin can significantly improve bone mass in osteoporosis, but the underlying mechanism with citrate is still unknown. Herein, we demonstrated that melatonin increased the bone volume along with the content of citrate in osteoporosis mice. Melatonin increased the citrate and mineralized nodules in osteoblasts induced from primary mouse bone marrow mesenchymal stem cells in vitro. ZIP-1 Knockdown and over-expression confirmed melatonin specifically up-regulated ZIP-1 to rescue citrate and bone mass. In general, we verified that melatonin can improve bone mass by enhancing matrix mineralization which is highly related to the increased secretion of citrate in osteoblasts, and ZIP-1 is the target of melatonin. It reveals another direction of melatonin regulating bone remodeling, and provides a research base for its possible application in the treatment of clinical osteoporosis in the future.